The effects of ischemic preconditioning on human exercise performance - Incognito, A. V.; Burr, J. F.; Millar, P. J. (Sports Medicine, 2016)
Ischemic preconditioning (IPC) is the exposure to brief periods of circulatory occlusion and reperfusion in order to protect local or systemic organs against subsequent bouts of ischemia. IPC has also been proposed as a novel intervention to improve exercise performance in healthy and diseased populations.